2019
DOI: 10.15218/edj.2019.06
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative evaluations of topography for CAD/CAM all ceramic zirconia after different surface treatments

Abstract: Background and objectives: The purpose of this in vitro study was to evaluate the effect of grinding, reglazing and polishing procedures on the surface roughness of monolithic zirconia qualitatively and quantitatively. Materials and methods: Thirty-six disc-shaped yttrium-stabilized zirconium oxide specimens were milled from pre-sintered zirconia blanks using CAD-CAM machine with a diameter of 12mm and thickness of 1.4mm for twenty-seven discs while 12mm and 1.2mm for nine discs as a control group. After that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Our results were also in conformity to a study performed by (62) which proved that the glazed full-contour zirconia (monolithic zirconia) have better result than other surface treatment. Our results were in line with previous study by, suggesting that glazing may not be as effective as it could be because the coating layer is not thick enough to adequately fill up the grooves and microcracks on the ceramic surface (63). Another study was done by (64) demonstrated that monolithic zirconia glazing performed lower than alternative surface treatments.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were also in conformity to a study performed by (62) which proved that the glazed full-contour zirconia (monolithic zirconia) have better result than other surface treatment. Our results were in line with previous study by, suggesting that glazing may not be as effective as it could be because the coating layer is not thick enough to adequately fill up the grooves and microcracks on the ceramic surface (63). Another study was done by (64) demonstrated that monolithic zirconia glazing performed lower than alternative surface treatments.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, glazing did not result in minimizing of surface roughness as efficiently as polishing, and this can be because coating layer was not adequately thick for the completion of the grooves and micro-cracks of ceramic effectively as stated by (Azez and Salih, 2019; Hashim and Mansoor, 2021), [23,24].…”
Section: Discussionmentioning
confidence: 66%
“…by using rotary equipment. [37] In our study, surface polishing was chosen for all fabricated restorations of both tested groups. [9] For chipping documentation in this study modified USPHS criteria were used as they provide reliable information regarding the overall long-term success of the restorations.…”
Section: Discussionmentioning
confidence: 99%